The Charter Granted by Their Majesties King William and Queen Mary to the Inhabitants of the Providence of the Massachussets Bay in New England 189-90 (1726) - (:unkn) unknown (My University, 1715)
An Act For Erecting a Powder-House within the Town of Boston: That, from and after the publication hereof, any person within the town of Boston, that shall presume to keep, in his house or Warehouse, any powder, above what is by law allowed, shall forfeit and pay, for every half-barrel, the sum of five pounds . . . That any person or persons whosoever, that shall throw any squibs, serpents, or rockets, or perform any other fireworks within the streets, . . (shall be fined).
Keywords: GUNPOWDER - STORAGE